Becoming and being a musician: The role of creativity in students’ learning and identity formation - Reid, A.; Bennett, Dawn (International Society for Music Education, 2014)
Students develop knowledge of themselves, their peers and their creative thinking and practice through a complex set of negotiations and experiences. Most students at a conservatorium enter with a long experience of music making in school, co-curricular activities and the home. They have learned to practice, to perform, and to think in musical ways; but at the tertiary level they have made an extra commitment to the ideal of becoming a professional musician. Students’ musical identity is in a fluid state as they develop from expert musical learner to novice professional musician. This transition is informed by students’ study experiences, which in turn inform their formation of professional identity and their negotiation of the relationships between the personal and the professional. In this study we explored the role of creativity in students’ learning and identity formation. The study was located at an Australian conservatoire where creativity is considered a graduate attribute and is also used as an assessment criterion. The study explored creativity as a single dimension of students’ developing professional ideas. Students were invited to participate in a discussion of what creativity means in relation to their learning. The discussion had minimal intervention by a facilitator, with students taking the lead on the discussion’s direction and outcomes.Using a linguistic approach, this paper examines how students negotiated views on creative thinking and practice. It shows how the forms of music students played or composed, and the affordances of their degree programs, mediated students’ creative activities. The discussion indicates what students see as the utility of creative practice or thinking for their future careers. Of interest are the moves and countermoves made between the students as they discuss elements of musical activity, thinking, performance, perceptions of musical genres and potential work environments. The moves and countermoves represent a form of knowledge transfer and co-construction in action.